The effect of oxidation on the subsurface microstructure of a Ti-6Al-4V alloy. (15th April 2018) - Bagot, P.A.J.; Radecka, A.; Magyar, A.P.; Gong, Y.; Bell, D.C.; Smith, G.D.W.; Moody, M.P.; Dye, D.; Rugg, D.
Abstract: Atom Probe Tomography (APT) and Transmission Electron Microscopy (TEM) are combined for examining α-case formation in Ti-6Al-4V, generated by air exposure at 800 °C. Below the oxide surface, the microstructure separates into a nanoscale mixture of the α-Ti and α2 Ti3 Al phases, of compositions Ti70-O30 and Ti65-O10-Al20-V5 respectively. The α2 phase exists either as bands or as nanoscale spherical precipitates. Nitrogen also penetrates the surface, but to a lesser extent, while vanadium partitions to α2 or in distinctly separate phases. The results demonstrate that oxygen stimulates precipitation of α2, helping to explain embrittlement produced in the O-enriched layer beneath the oxide. Graphical abstract: Unlabelled Image